Fiqh al-saraya - al-'Isawi, Mahmud Khalaf Jarad ('Amman : Dar'Ammar, 2000)
Detachment in Islamic law; Muḥammad, Prophet, d. 632; military activity
Keywords: Muhammad, -- Prophet, -- d. 632 -- Military leadership; War (Islamic law); Military law (Islamic law)